Beeldenroute 4. - Beeldenroute Diepenheim 1986 (Diepenheim : Stichting Beeld-en-Route, 1986)
van Meurs, Sien ; van der Zwaag, Gonda ; Lamberts, Aart ; de Wit, Niko ; Sillen, Cees ; Varkevisser, Ernst ; Visser, Nout ; de Fluiter, Adri ; Nap, Jan ; Lamberts, Aart ; Duval, Maïté ; Homan, Jetty ; Blaauw, Gjalt ; Volten, André ; Bolink, Frank ; Schole, Harald ; van der Kloot, Hetty ; Varkevisser, Ernst ; van Meurs, Sien ; van Bennekum, Henk ; Oelen, Henk ; de Wit, Niko ; etc.
Beeldenroute 4, Diepenheim, 7 mei t.m 14 september 1986
boek